Spectres in the Subcontinent: Victorian Gothic Narratives and the Shadow of Contemporary Indian Cultural Anxieties - Smitha G.L. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Victorian Gothic literature emerged during a period of profound social transition marked by industrialization, scientific advancement, imperial expansion, and moral anxiety. Texts such as Dracula, Frankenstein, Wuthering Heights, and The Woman in White expose hidden fears surrounding degeneration, fractured identities, gender transgression, and social surveillance. While traditionally read within a European framework, these Gothic anxieties find striking resonance within the cultural and psychological landscapes of contemporary India, particularly in the context of globalization, digital transformation, and shifting moral paradigms. This paper explores how Victorian Gothic narratives metaphorically reflect emerging Indian realities such as urban alienation, inherited trauma, patriarchal authority, caste-based marginalization, and the negotiation between tradition and modernity. The Gothic "monster," "madwoman," and "haunted space" are reinterpreted as symbolic representations of suppressed voices, invisible labour, and generational anxieties embedded in Indian social structures. By drawing parallels between the Victorian obsession with respectability and modern India’s preoccupation with social image, honour, and digital performativity, the study demonstrates how Gothic tropes continue to function as cultural diagnostics. Employing a post-truth theoretical lens, this paper analyses how contemporary Indian narratives across literature, cinema, and digital storytelling replicate Gothic strategies of fear, secrecy, and fragmented identity to articulate socio-political disquiet. The research highlights the relevance of Gothic discourse in understanding modern India’s struggles with gender violence, mental health stigmatisation, ecological crisis, and the loss of cultural authenticity in hyper-mediated spaces. By repositioning Victorian Gothic fiction within the Indian socio-cultural continuum, this paper asserts that Gothic literature transcends temporal and geographic boundaries, functioning as a living narrative mode that articulates collective anxieties in rapidly transforming societies. It ultimately argues that the Gothic remains a powerful critical framework for interpreting emerging cultural realities in 21st-century India.